Sei sulla pagina 1di 10

(t) > T = 0

Γ 12 (0) =< E 1 (t) E

|γ˜ 12 (0)|

˜

˜

˜

2

< I 1 (t + τ)I 2 (t) > T =< I 1 > T < I 2 > T [1

+

|γ˜ 12 (τ)| 2 ]

I 1 (t) = I 1 (t)< I 1 > T < I 1 (t) > T = 0 I 2

< I 1 (t + τ )∆I 2 (t) > T =< I 1 > T < I 2 > T |γ˜ 12 (τ)| 2

)∆ I 2 ( t ) > T = < I 1 > T < I

h = 0

• λ = 635 nm

λ = 635nm

• • • • • • •

µs

• µs • G ( 2 ) G ( 2 ) = < I 1 I

G (2)

G (2) =

< I 1 I 2 >

< I 1 >< I 2 >

G (2)

G (2) =< I 1 I 2 >

G (2) M G (2)

G ( 2 ) G ( 2 ) G ( 2 )

G (2)

G ( 2 ) G ( 2 ) G ( 2 )

G (2)

G (2)

G (2) G (2)

G ( 2 ) G ( 2 ) G ( 2 ) G ( 2 )

G (2)

G (2) G (2)